OPERATIONAL PERFORMANCE ANALYSIS OF PUBLIC BUS TRANSPORT SERVICES IN ADDIS ABABA, ETHIOPIA - Mulugeta GIRMA (Scientific Journal of Silesian University of Technology. Series Transport)
In emerging countries, improving performance in the transportation industry is a critical concern. Bus transport companies like Anbessa, Sheger and the Public Service Employees' Transport Service play a pivotal role in Addis Ababa's transit system. Subsequently, this study analyzes the operators' operational performance, comparing it to industry norms. The collected data is analyzed using the ratio analysis approach. The findings indicate that the Anbessa City Bus outperforms the other buses in several aspects, such as fleet strength, service utilization, and vehicle utilization, but there is a disparity in staff productivity and operational safety. Sheger City Bus, on the other hand, outperforms the market in terms of vehicle utilization, workforce productivity, and operational safety. However, on most of the indicators, the Public Employees Bus performs the worst. Finally, comparing the operators' performance to industry standards, most indications show that they fail to meet. Consequently, even if bus transit operators are subsidized by the government in the operation of their services for residents, the study suggests that they must make significant improvements in how they use their resources to improve their financial and operational performance and deliver better services compared to those provided by other operators in the city. In addition, government incentives such as subsidies should be allocated based on actual operational performance.